2018
DOI: 10.1093/nar/gky532
|View full text |Cite
|
Sign up to set email alerts
|

Intron-containing algal transgenes mediate efficient recombinant gene expression in the green microalga Chlamydomonas reinhardtii

Abstract: Among green freshwater microalgae, Chlamydomonas reinhardtii has the most comprehensive and developed molecular toolkit, however, advanced genetic and metabolic engineering driven from the nuclear genome is generally hindered by inherently low transgene expression levels. Progressive strain development and synthetic promoters have improved the capacity of transgene expression; however, the responsible regulatory mechanisms are still not fully understood. Here, we elucidate the sequence specific dynamics of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
182
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(190 citation statements)
references
References 56 publications
7
182
0
1
Order By: Relevance
“…Compared to BKT from other organisms, the CrBKT contains a long peptide extension on its C-terminus (Figure 1c), which appears to be an unfolded peptide region. Here, we took the CrBKT sequence and used our recently developed transgene optimization strategy (Baier et al, 2018b) to enable its re-integration into the algal nuclear genome and overexpression. When CrBKT was expressed, it caused the green algal cells to noticeably change colour from green to red, indicating the conversion of carotenoids to ketocarotenoids, with astaxanthin representing a major component of these.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to BKT from other organisms, the CrBKT contains a long peptide extension on its C-terminus (Figure 1c), which appears to be an unfolded peptide region. Here, we took the CrBKT sequence and used our recently developed transgene optimization strategy (Baier et al, 2018b) to enable its re-integration into the algal nuclear genome and overexpression. When CrBKT was expressed, it caused the green algal cells to noticeably change colour from green to red, indicating the conversion of carotenoids to ketocarotenoids, with astaxanthin representing a major component of these.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that transgenes could be optimized for expression from the algal nuclear genome by codon optimization and systematic incorporation of the first intron of the C. reinhardtii RuBisCO small subunit II gene to mimic host regulatory structures (Baier et al, 2018b). We have recently used this strategy for overexpression of numerous foreign genes (Lauersen et al, 2016;Lauersen et al, 2018;Wichmann et al, 2018) , as well as re-coding and overexpression of the endogenous photodecarboxylase (CrFAP) (Yunus et al, 2018) for various metabolic engineering activities in this host.…”
Section: Intragenic Expression Of β-Ketolase In C Reinhardtiimentioning
confidence: 99%
See 2 more Smart Citations
“…The nucleotide sequence of C. reinhardtii Hy5 (Uniprot: A0A2K3DRN7) was optimized as previously described (Baier et al, 2018) using the Intronserter tool (Jaeger et al, 2019) (https://bibiserv.cebitec.uni-bielefeld.de/intronserter). The codon optimized, intron containing gene was chemically synthesized (GenScript, Piscataway Township, New Jersey) and cloned between Bam HI- Bg lII or Eco 32I- Eco RI in the pOpt2_mVenus_Paro vector (Wichmann et al, 2018).…”
Section: Methodsmentioning
confidence: 99%